Biofilm visualization as a component of the procedure of individual and professional tooth brushing. (Literature Review) - Chumakova Юлія Геннадіївна; Antoshchuk Вероніка Олегівна (Actual Dentistry, 2023)
Introduction. Dental plaque is a structured microbial biofilm on the surface of tooth enamel, which is usuall transparent and practically invisible to the naked eye. Therefore, special dyeing solutions or tablets, the so called "disclosing agents" or "plaque indicators", are used for visualization and identification of biofilm. They make it possible to clearly see the presence of plaque, to determine its location and thickness on various surfaces of the tooth, including in hard-to-reach areas. Purpose: based on the analysis of scientific articles, to determine the composition, properties of various plaque indicators and to assess their effectiveness during individual and professional oral hygiene. Materials and methods. Informational search and analysis of scientific literature was carried out using scientometric databases Web of Science, PubMed, Google Scholar mainly over the past 10 years, but the review also includes sources that reveal historical facts and trends in the development of modern dental plaque indicators. Conclusion. Visualization of dental plaque using special disclosing solutions, tablets, gels is one of the easiest and fastest ways to objectively detect microbial biofilm. Currently, two-color plaque indicators are preferred, which allow setting the formation term or "maturity" of the biofilm. The results of numerous scientific studies presented in the review confirm the high effectiveness of plaque indicators in conducting individual and professional oral hygiene in children and adults. Their application significantly improves the motivation of patients for the qualitative removal of dental biofilm.